Filetierversuche an antarktischen Fischen - Papajewski, H.; Schreiber, W. (1978)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010